Open 'Hearing' in a Closed Sea: Migration Policies and Postcolonial Strategies of Resistance in the Mediterranean. Issue 1 (2nd January 2016) - Palladino, Mariangela; Gjergji, Iside
Abstract : In the early 2000s migration towards Italy, both as a destination and transit country, was on the rise and gained increasing importance on the political agenda. In this context, enhanced security measures of border control in the Mediterranean became a priority. Meanwhile, new forms of postcolonial resistance have emerged as Italy has been compelled to face its long-standing colonial amnesia. The 2012 documentary film Mare Chiuso (Closed Sea) captures a slice of the entangled discourses, politics and practices in the Mediterranean. It recounts the story of boat migrants who set off from Libya in May 2009 and were forced back to their point of departure by Italian authorities. Engaging with the testimonies of the migrants involved, as well as with the legal discourses surrounding the case, Mare Chiuso brings to the fore the emerging contradictions at play in dominant discursive practices. The film offers alternative perspectives from the margins, problematizes official narratives and instigates fruitful debates on the Mediterranean as a geopolitical and cultural site. Traversing postcolonial and cultural studies, political science and law, this essay proposes an analysis of Mare Chiuso as an instance of postcolonial resistance. Independent and separate disciplinary approaches have failed successfully to map and investigate complex phenomena such as migration; thus, this essay brings into contact cultural theory and legal discourses with the aim of better understanding the burgeoning postcolonial phenomena in contemporary Italy.